Imprisoning Yoga: Yoga Practice May Increase the Character Maturity of Male Prison Inmates - Kerekes, Nóra; Brändström, Sven; Nilsson, Thomas (Frontiers in Psychiatry, 2019)
Background: A specific personality profile, characterized by low character maturity (low scores on the Self-Directedness and Cooperativeness character dimensions) and high scores on the Novelty Seeking temperament dimension of the Temperament and Character Inventory (TCI), has been associated with aggressive antisocial behavior in male prison inmates. It has also been shown that yoga practiced in Swedish correctional facilities has positive effects on inmates’ well-being and on risk factors associated with criminal recidivism (e.g. antisocial behavior). In this study we aimed to investigate whether the positive effect of yoga practice on inmates’ behaviors could be extended to include eventual changes in their personality profile. Methods: Male prison inmates (N=111) in Sweden participated in a randomized controlled 10-week long yoga intervention trial. Participants were randomly assigned to either a yoga group (one class a week; n=57) or a control group (free of choice weekly physical activity; n=54). All the inmates completed the TCI questionnaire before and after the intervention period as part of an assessment battery. Results: After the 10-week-long intervention period male inmates scored significantly lower on the Novelty Seeking and the Harm Avoidance and significantly higher on the Self-Directedness dimensions of the TCI. There was a significant medium strong interaction effect between time and group belonging for the Self-Directedness dimension of character favoring the yoga group. Conclusion: A 10-week-long yoga practice intervention among male inmates in Swedish correctional facilities increased the inmates’ character maturity, improving such abilities as their capability to take responsibility, feel more purposeful and being more self-acceptant – features which previously were found to be associated with decreased aggressive antisocial behavior.